Investigation of bidirectional converter utilizing battery energy storage for an isolated load system - Nagarajan Karthikeyan; G. D. Anbarasi Jebaselvi David (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
To explore the design of a bidirectional isolated converter for usage with battery energy storage systems, the study aims to analyses this investigation. The change resulted in a reduced workload, which is an obvious advantage. We instead think that there will be no effect on the load-carrying capacity due to the increase in production. This research provides an alternating-direct-current renewable energy supply system. Solar, wind, power storage, and a load are included. This is an in-depth discussion of a power conversion converter's control system. Using an energy storage device in addition to the controller is feasible (ESSs). This research resulted in adaptive PI control, which is known for lowering link voltage and faster responses. Using this control system, you can cut down on both transient and static issues and also have a better shot at minimizing defects. MATLAB/Simulink is an application which does simulations. To evaluate the efficacy of an envisioned system, one simulates the systems and compares the results. The results show that the hybrid power supply model proposed may have a substantial effect on the energy supply to the isolated load and can be utilized to build a unique plan for a green data center.